Traumatic Metachronous Penile Fracture to the Contralateral Corpora - Christos Papaioannou; Savvas Omorphos (Case Reports in Surgery)
Penile fracture is an uncommon condition in day-to-day urological practice. Though most cases of penile fracture are traumatic in nature, these are typically unilateral. Synchronous bilateral cases have been rarely reported. We present the third case recorded to date, to the best of our knowledge, of a metachronous penile fracture to the contralateral corpora due to trauma related to sexual intercourse. The first presentation demonstrated a significant tear to the left corporal body at surgical exploration that was repaired. There was no postoperative complications or erectile dysfunction on outpatient follow-up. Six months thereafter, the patient had another similar presentation and demonstrated a right corporal body fracture which was repaired surgically on an urgent basis. Prompt diagnosis and low threshold for surgical intervention are essential to reduce morbidity and prevent long-term complications.